Integration of ESG Information Into Individual Investors’ Corporate Investment Decisions: Utilizing the UTAUT Framework - Park, So Ra; Oh, Kum-Sik (Frontiers in Psychology, 2022)
Environmental, Social, and Governance (ESG) criteria are now considered significant, global non-financial evaluating factors of corporate value. However, no attention is given to what influences the integration of ESG information by individual investors’ in their investment decisions. This study first identifies different types of information investors use to make investment decisions. Next, the Unified Theory of Acceptance and Use of Technology (UTAUT) model is used to identify individual investors’ investment tendencies and the factors affecting integration of ESG information into investment decisions. Each of four categories for UTAUT innovation adoption factors (performance expectancy, effort expectancy, social influences, and facilitating conditions) are discussed in relation to how they affect individual investors’ integration of ESG information. Standardization of ESG reporting and evaluation frameworks would reduce efforts to adopt ESG information, and could build a strong foundation for facilitating ESG information integration. Corporates’ efforts to further communicate their ESG management through their investor relations and active governmental well as non-governmental organizations’ participation are recommended.